PATH-45. CLINICAL UTILITY OF COMBINED NEXT GENERATION SEQUENCING AND CHROMOSOMAL MICROARRAY ANALYSIS FOR THE DIAGNOSIS AND MANAGEMENT OF ADULT GLIOMAS. (9th November 2020) - Praska, Corinne; Kollmeyer, Thomas; Fritcher, Emily Barr; Voss, Jesse; McKenna, Michelle; Balcom, Jessica; Pryzbylski, Amber; Pasion, Romela; Kipp, Benjamin; Raghunathan, Aditya; Vaubel, Rachael; Passow, Jeanette Eckel; et al.
Abstract: BACKGROUND: Molecular parameters have been incorporated into the 2016 WHO Classification of CNS Tumors and subsequent cIMPACT-NOW updates to facilitate clinical management of glioma patients. However, there have been few reports of the overall clinical utility of comprehensive genetic testing in adult glioma patients. We report the results of sequencing and chromosomal microarray analysis of adult gliomas seen at the Mayo Clinic and through the Mayo Clinic Laboratories (MCL) reference practice. METHODS: A consecutive series of 379 Mayo Clinic adult glioma patients were consented to receive targeted next generation sequencing and chromosomal microarray analysis, regardless of standard clinical ordering practices. Known diagnostic, prognostic, and predictive alterations were annotated for each case. These results were compared to the larger MCL reference practice of 2400 adult glioma samples that received one or both tests clinically. RESULTS: Of the consecutive Mayo Clinic cases, 67% had alterations that fell into at least one of the diagnostic, prognostic, and/or predictive categories. Molecular testing generated diagnostic, prognostic, and predictive information in 44%, 34%, and 36% of cases, respectively. Diagnostically, molecular testing mainly aided in arriving at a final integrated diagnosis, and only a small number of cases (n= 5; 1%) had a change in diagnosis. The consecutive cases represent the typical distribution of adult glioma types (47% IDH-wildtype glioblastoma/astrocytoma, 22% IDH-mutant astrocytoma/glioblastoma, 13% IDH-mutant 1p/19q-codeleted oligodendroglioma, and 18% other tumor types). The MCL practice is enriched in tumors with atypical molecular patterns (37% IDH-wildtype glioblastoma/astrocytoma, 17% IDH-mutant astrocytoma/glioblastoma, 18% IDH-mutant 1p/19q-codeleted oligodendroglioma, and 29% other tumor types). CONCLUSIONS: Molecular testing provides useful diagnostic, prognostic, and predictive information for the clinical management of adult glioma patients. While the current guidelines for ordering molecular testing are effective for diagnostic purposes, additional prognostic and predictive information can be gleaned from comprehensive molecular testing of adult gliomas.